Syntaxin-1a is a Direct Target of miR-29a in Insulin-producing β-Cells - Bagge, A.; Dahmcke, C. M.; Dalgaard, L. T. (Hormone and Metabolic Research, 2013)
Downregulation of proteins involved in the exocytotic machinery has been implicated in the impairment of normal β-cell function in response to high glucose levels. Syntaxin-1a (Stx-1a) is one of two t-SNAREs involved in insulin exocytosis and decreased expression of Stx-1a protein impairs glucose-stimulated insulin secretion (GSIS) in isolated rat pancreatic islets. In diabetic patients Stx-1a protein levels are reduced, but the mechanism of this suppression is unknown.MicroRNAs are small noncoding RNAs, which are important regulators of gene-expression at the post transcriptional level, partially binding to the 3′UTRs of their target gene transcripts either mediating transcript degradation or inhibiting translation. We have recently shown that miR-29a is upregulated in response to elevated glucose levels in β-cells and is involved in mediating the negative effect of high glucose levels on GSIS. Stx-1a has a predicted target site of miR-29a present in its 3′ untranslated region. The objective of this study was to evaluate whether miR-29a targets Stx-1a directly to decrease mRNA and/or protein levels in response to glucose. Stx-1a mRNA and protein levels decreased in β-cells treated with increased glucose levels. Overexpression of miR-29a decreased Stx-1a mRNA and protein levels. Furthermore, miR-29a decreases the response of a luciferase reporter construct containing the predicted target site normally present in the Stx-1a gene. When 2 nucleotides are mutated in this target site, responsiveness to miR-29a disappears, confirming miR-29a binding to this sequence. Collectively, these data implicate miR-29a as a mediator of glucose-induced downregulation of Stx-1a in β-cells.